Swim back to me [large type] - Packer, Ann, 1959- (Center Point Large Print, 2011)
A collection of burnished, impossible-to-put down narratives: A wife struggles to make sense of her husband's sudden disappearance. A mother mourns her teenage son through the music collection he left behind. A woman shepherds her estranged parents through her brother's wedding and reflects on the year her family collapsed. A young man comes to grips with the joy and vulnerability of impending fatherhood. Two teens forge a sustaining friendship, only to discover the disruptive and unsettling power of sex.